ATH-02 External validation and comparison of outcomes for two scoring systems for lower gastrointestinal bleeding. Issue 2 (June 2019) - Smith, Christopher; Leggett, Gillian; Jayaprakash, Anthoor; Khan, Mohammed; Thomson, John; Vijayan, Balasubramaniam; Fraser, Andrew; Leeds, John
Abstract : Introduction: Lower gastrointestinal bleeding (LGIB) is a common and heterogeneous condition. We have previously reported on a prognostic scoring system devised from the Aberdeen cohort and recently another scoring system has been published (The Oakland score) but requires validation. 1 Both scoring systems report the ability to identify low risk of rebleeding and mortality at 30 days. This study aimed to compare the two scores particularly with respect to identifying those who may be eligible for safe discharge from a bleeding point of view. Methods: The Aberdeen bleeding unit database was used (N=2719) to derive and internally and validate our scoring system using the following variables; inpatient status, age, syncope, underlying malignancy, liver disease, blood pressure, pulse rate and haemoglobin. The score was then externally validated in a different region. The Oakland score was then applied to the derivation cohort and receiver operating characteristic (ROC) curves calculated and compared with the Aberdeen score. To determine each scores ability to identify low risk patients, an Aberdeen score of <1 was compared with an Oakland score <9 (both determined a priori) to assess rebleeding and mortality rates at 30 days. Results: The derivation cohort of 2385 patients (1140 males) was used to compare the two scores of whom 129 (5.6%) patients died within 30 days, 135 (5.7%) required surgical intervention and 322 (13.5%) experienced re-bleeding. Comparing the two scoring systems with respect to rebleeding showed an area under the ROC curve of 0.742 (0.709 – 0.774) for the Aberdeen score and 0.687 (0.668 – 0.705) for the Oakland score. With respect to mortality the area under the ROC curve was 0.802 (0.755 – 0.848) for the Aberdeen score and 0.757 (0.739 – 0.774) for the Oakland score. An Aberdeen score <1 was associated with a significantly lower 30 day rebleeding risk compared to an Oakland score <9 (4/379 (1.1%) vs. 15/355 (4.2%), p=0.009) but 30 day mortality was similar (0/365 (0.0%) vs. 1/355 (0.3%), p=0.493). Conclusion: The use of these scores may predict who can be safely discharged. The Aberdeen score is easier to calculate on admission and appears to be superior to the Oakland score, particularly for predicting rebleeding.. Prospective evaluation of both scores is required. Reference: Oakland K, Jairath V, Uberoi R, Guy R, Ayaru L, Mortensen N, Murphy MF, Collins GS. Derivation and validation of a novel risk score for safe discharge after acute lower gastrointestinal bleeding: a modelling study. Lancet Gastroenterol Hepatol 2017 Sep;2(9):635–643.